Assessing the Impact of using biofloc system with different feeding rates on Nile Tilapia (Oreochromis niloticus) Performance - MAGOUZ, F.I.; EL-HAMADY, A.K.; MOUSTAFA, E.M.; MANSOUR, A.I.A. (Journal of the Hellenic Veterinary Medical Society, 2021)
Biofloc technology is a technique of enhancing water quality in aquaculture through balancing carbon and nitrogen in the system. Randomly designed 3×1 factorial treatments for 90 days was conducted;to assess the effects of biofloc technology in indoor tanks for Nile tilapia (Oreochromis niloticus); on the growth performance, digestive enzyme activity, hematology, immune response, intestinal morphometry and chemical composition of Nile tilapia and flocs. In addition, to distinguish the best feeding; through utilizing different feeding rate 0.5%, 1% and 1.5% rate; with zero water change (biofloc technique; BFT) and their impact on aquatic animal rearing. Fish were reared in nine fibreglass indoor tanks (2 m3/ each); three replicates / treatment (feeding rate) with 100 fish / tank. Diets were offered twice / day. Results showed that values of water parameters were optimal for tilapia culture and the recorded ammonia, nitrite and nitrate concentrations are created through nitrification process in the BFT system. BFT protein increased positively with increased feeding rate, while BFT lipid and carbohydrates negatively decreased. Growth performance and feed utilization efficiency were significantly improved by increased feeding rates however; the best food conversion rate was recorded in 0.5% feeding rate treatment.There was negative relationship between crude protein and fat contents in fish body; with the highest crude protein content in 1.0% feeding rate treatment. The overall improvement in haematological and serum biochemical parameters reflects the positive effect of biofloc system on the physical condition and immune response of tilapia.The total intestinal length and intestinal villi heights were significantly increased with decreased feeding rate; with highest length in 0.5% feeding rate treatment. In conclusion, using BFT in tilapia rearing with 0.5% feeding rate, had beneficial effects on maintaining good water quality, improving feed utilization and growth performance, increasing fish body protein content, physical and immune response promotion as well as increasing the absorptive capacity of the intestine. Subsequently, BFT offers not only economic benefits for fish farmers and safe product for consumers but also, for the sustainability of the fish environment.